Anti-Oxidative, Anti-Inflammatory and Anti-Apoptotic Effects of Flavonols: Targeting Nrf2, NF-κB and p53 Pathways in Neurodegeneration - Maja Jazvinšćak Jembrek; Nada Oršolić; Lucija Mandić; Anja Sadžak; Suzana Šegota (MDPI AG, 2021)
Neurodegenerative diseases are one of the leading causes of disability and death worldwide. Intracellular transduction pathways that end in the activation of specific transcription factors are highly implicated in the onset and progression of pathological changes related to neurodegeneration, of which those related to oxidative stress (OS) and neuroinflammation are particularly important. Here, we provide a brief overview of the key concepts related to OS- and neuroinflammation-mediated neuropathological changes in neurodegeneration, together with the role of transcription factors nuclear factor erythroid 2-related factor 2 (Nrf2) and nuclear factor-κB (NF-κB). This review is focused on the transcription factor p53 that coordinates the cellular response to diverse genotoxic stimuli, determining neuronal death or survival. As current pharmacological options in the treatment of neurodegenerative disease are only symptomatic, many research efforts are aimed at uncovering efficient disease-modifying agents. Natural polyphenolic compounds demonstrate powerful anti-oxidative, anti-inflammatory and anti-apoptotic effects, partially acting as modulators of signaling pathways. Herein, we review the current understanding of the therapeutic potential and limitations of flavonols in neuroprotection, with emphasis on their anti-oxidative, anti-inflammatory and anti-apoptotic effects along the Nrf2, NF-κB and p53 pathways. A better understanding of cellular and molecular mechanisms of their action may pave the way toward new treatments.